2018
DOI: 10.1590/0104-1428.08017
|View full text |Cite
|
Sign up to set email alerts
|

Stability and rheological behavior of coconut oil-in-water emulsions formed by biopolymers

Abstract: Proteins are frequently used as emulsifiers and stabilizers. In this work, two proteins with different isoelectric points were used: lactoferrin and ovalbumin. Solutions containing different proteins ratios, with different pH values, were stored for 7 days at 25 °C to analyze the system stability. Systems containing 3% w/v lactoferrin remained stable at all pH values studied, while systems containing 1% w/v ovalbumin remained stable only at a high pH value (8.0). Emulsions containing a mixture of proteins rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The time constant ( K ) is related to emulsion instability (creaming). Thus, emulsions showing longer times showed greater stability due to strong drop-drop interactions, which can also be observed in Reference [ 17 ].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The time constant ( K ) is related to emulsion instability (creaming). Thus, emulsions showing longer times showed greater stability due to strong drop-drop interactions, which can also be observed in Reference [ 17 ].…”
Section: Resultssupporting
confidence: 72%
“…The stability of the emulsion also depends on the molecular weight of the protein and polysaccharides used as stabilizers, their charge, concentration, ionic strength, pH, and temperature [ 11 , 12 , 13 , 14 ]. The rheological properties of protein-stabilized emulsions differ from Newtonian, showing differentiated behaviors [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings, Gulão et al. described the behavior of coconut O/W emulsions as pseudoplastic (Gulão, Souza, Costa, Rocha‐Leão, & Garcia‐Rojas, 2018).…”
Section: Resultssupporting
confidence: 92%
“…Studies have already shown the effect of different homogenization pressures and their response to the stability of the emulsion (Cheng et al, 2020;Matsuura et al, 2015). Other types of processing have been used to prepare ultrasonic emulsions that have shown excellent results in reducing particle size and excellent morphologies: particles of uniform size that favor emulsions and, consequently, avoid coalescence (Gulão et al, 2018;X. Lu, Su, et al, 2019b;Ramisetty et al, 2015;Saricaoglu et al, 2018).…”
Section: Stability Of Oil-in-water Emulsion Systemsmentioning
confidence: 99%